Avaliação do Sistema de Monitoramento Computadorizado de Digestão in Vitro. 1. Testes Preliminaires - De Campos, Fábio Prudêncio [UNESP] (2000)
The objective of this work was to test the computerized monitoring of the in vitro gas production system. This technique made easy the degradation studies of soluble and insoluble fractions of forages, determined by the gas production (CO 2 e CH 4) from microbial metabolism and measured by a pressure sensor. Several amounts of samples (50 to 110 mg of alfalfa hay) and other feedstuffs were tested. Also, the influence of the amount of ruminal liquid (2.0 or 3.0 mL), with or without stirs in incubator flasks, on the digestibility of 100 mg of alfalfa hay, was studied. The amount of 100 mg of sample, 2.0 mL of ruminal liquid and without agitating magnetic bar, provided lower coefficients of variance on the gas production. In conclusion, 2.0 mL of ruminal liquid, without stirrer with 100 mg of sample, presented a greater precision of the digestion curve.